Web-Based Land and Building Tax Records Information System - Yuniarti, Yuniarti; Utami, Alia Tri; F, Ganjar Nurul; Suwarno, Adi (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
The property tax registration process in One of The Regions in Bandung is carried out manually, resulting in the reliance on books and archiving in cabinets for information registration. The PBB registration process also includes inputting and reporting information through personal calls made via social media chat. This process especially demands citizens to physically visit the village without possessing an official letter when they receive a call. The absence of written proof when contacting the inhabitants causes them to feel anxious and uncertain, resulting in physical fatigue for the village staff. The Property Tax registration information system can oversee the data recording process for all system users (administrators, operators, visitors), including data recording, biodata recording, village services, and calling operations. Furthermore, residents can access and examine this information system via the Internet, enabling efficient monitoring and viewing of relevant data.